ANALISIS PENGARUH PENGALAMAN KERJA, DISIPLIN KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI SMA N 1 KARANGRAYUNG KABUPATEN GROBOGAN - M. Budiyono; Kasidin (Media Akuntansi, 2022)
This study purpose was determined the effect of work experience, work discipline and leadership style on employee performance at SMA N 1 Karangrayung, Grobogan Regency. The study was used descriptive and verification research with a total sample of 61 people. The sampling method used the saturated sampling method. Data collection methods are questionnaires and observation. The research instrument used a Likert scale. The data analysis methods were used descriptive tests, data quality tests, namely validity and reliability tests, multiple linear regression analysis, hypothesis testing (t test), model test (f test) and multiple determination coefficient test (R2). The conclusions obtained in this study are 1) Work experience has a positive and significant effect on employee performance at SMA N 1 Karangrayung, Grobogan Regency, 2) Work discipline has a positive and significant effect on employee performance at SMA N 1 Karangrayung, Grobogan Regency, and 3) Leadership style has a positive effect and significant to the employees performance of SMA N 1 Karangrayung, Grobogan Regency.